INCREASING THE WORK PRODUCTIVITY BY CREATING WORK PROGRAMMES FOR CNC WOODWORKING CENTRE USING MACROS - Mladenova, Marina; Brezin, Bogomil (Innovation in Woodworking Industry and Engineering design, 2013)
This article presents the results of a research carried out by the authors of three different approaches of creating work programmes for universal woodworking machine center with computer control (CNC woodworking centre) on work productivity – input of operations by the CNC software, import from CAD software and using created macros. The analysis of the results proves that the programming and the use of macros greatly increases work effectiveness when creating work programmes for CNC woodworking centres which leads to increased productivity and competitive advantage.